Altruistic preferences of pre-service teachers: The mediating role of empathic concern and the moderating role of self-control - Li, Maohao; Li, Wei; Yang, Qun; Huang, Lihui (Frontiers in Psychology, 2022)
Empathy and altruistic behavior are more crucial abilities for pre-service teachers to possess when compared to other majors. The relationship between empathy and altruistic behavior in Chinese pre-service teachers and their underlying mechanisms, however, has received relatively little attention in the literature. Therefore, the goal of the current study was to examine the links among majors (i.e., pre-service teacher and non-pre-service teacher), self-control, emotional empathy (i.e., empathic concern) and altruistic preferences among undergraduates and graduates in five Chinese universities (roughly age from 18 to 26 years; 58.4 percent female) with the Interpersonal Reactivity Index-C Questionnaire, Self-Control Scale, and Chinese Self-Report Altruism Scale tests. The results showed that there is a significant difference between pre-service teachers and non-pre-service teachers in empathic concern and self-control. Furthermore, the empathic concern and altruistic behavior tendency of pre-service teachers were significantly higher than that of non-pre-service teachers. Furthermore, mediation analyses indicated that empathic concern partially mediated the relationship between majors and altruistic tendency, and moderated mediation analysis further revealed that self-control buffered the relation between empathic concern and altruistic behavior tendency. These results demonstrate that the altruistic tendency of pre-service teachers is influenced by empathic concern and self-control.